PANDANGAN EKONOMI ISLAM TERHADAP JUAL BELI MELALUI MARKETPLACE ONLINE SHOPEE - Ayesha Ayesha; Hasril Atieq Pohan (Yonetim Jurnal, 2023)
The background to this research is that the online marketplace Shopee is an online shopping platform that focuses more on user convenience, safety, fun and practicality by integrating social platforms. However, as times become increasingly modern, the business world increasingly tends to ignore ethics. In fact, growing competition leads to conflicting practices such as fraud, lies, non-conforming goods. Just because to get as much profit as possible. The aim of this research is to find out how buying and selling in the Shopee online marketplace and buying and selling through the Shopee online marketplace according to a review of Islamic business ethics. In this research the author used a qualitative method with a descriptive approach. Data collection techniques in this research are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The location of this research is the online marketplace Shopee in Palembang City. The results of this research are that the Shopee online marketplace provides good service for its users and allows its users to shop anytime and anywhere, as long as there are facilities to access the internet. In Islamic business practices and economics are very closely related to Islamic creeds and sharia so that a person will not understand the Islamic view of economics and business without properly understanding creeds and Islam. Then the principles of honesty and accuracy are in line with the principle of truth, the principle of loyalty is in line with the principle of justice, and the principle of discipline is in line with the principle of responsibility. So it can be said that the principles of business ethics are in place and in line with the principles of Islamic business ethics. Trust is important for consumers, it is hoped that sellers can increase consumer trust and can improve the quality of content and services provided. For consumers, before carrying out online buying and selling transactions, it is best to dig deeper or look for as clear information as possible regarding the product specifications offered by the seller. For future researchers, it is recommended to take more samples, this aims to have better data accuracy in their research.